Psychobiome Feeding Mind: Polyphenolics in Depression and Anxiety - Matarazzo, Ilaria; Toniato, Elena; Robuffo, Iole (Current Topics in Medicinal Chemistry, 2018)
Recently gut bacterial populations seem to be involved in many functions and in the pathogenesis of several medical conditions. Traditionally the intestinal microbiome has been recognized to play an important role in metabolizing food compounds in simpler chemical structures for the absorption of different nutrients, and in maintenance control of gastrointestinal pathogens species. Bacterial populations are implicated in a complicated network of interactions within the immune system, epithelial cells local endocrine system, that affects the peripheral and the central nervous system, via blood circulation. Microbiome influencing the mind via immune, endocrine and metabolic signalling, is able to exert some clinical effects in different mental diseases. It releases endocrine substances through several pathways involved in the modulation of neuroinflammation and production of several neurotrasmitter precursors. It has recently been named psychobiome. It is known that phenolic compounds are able to influence microbiome proliferation and to exert several roles, especially regarding neuroinflammation in depressive and anxious behaviour. The clinical effects are reported in the literature. The aim of this study is to highlight the interaction between polyphenols and microbiota- gut-brain axis.
Keywords: Depression